Large-Scale Organizational ChangeLarge-Scale Organizational Change, by MohrmanAllan M.Jr.MohrmanSusan AlbersLedfordGerald E.Jr.CummingsThomas G.LawlerEdward E.IIIand Associates. San Francisco: Jossey-Bass, 1989, 314 pp., $28.95, hardcover. - Litzinger, William (Academy of Management Review, 1990)
The article reviews the book ?Large-Scale Organizational Change,? by Allan M. Mohrman, Susan Albers Mohrman, Gerald E. Ledford, Thomas G. Cummings and Edward E. Lawler.